2021
DOI: 10.1186/s13052-021-01092-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of home confinement on pediatric fractures during the COVID 19 outbreak

Abstract: Objective To control the transmission of coronavirus disease 2019 (COVID-19), the Chinese government encouraged people to stay at home. This study aimed to evaluate the effects of home confinement on the occurrence of fractures among children. Study design We retrospectively reviewed children admitted to Children’s Hospital of Chongqing Medical University, for traumatic injury from January 24 to March 10, 2020, and the same time period in 2017, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 16 publications
0
27
0
2
Order By: Relevance
“…The general exercise method is from simple to complex, time from short to long, frequency from less to more, the intensity of exercise gradually increases, and the transition from passive exercise to active exercise gradually [ 41 , 42 ]. It is appropriate for the child to accept and not cause severe pain, and if necessary, give appropriate analgesics in accordance with the doctor's instructions before the exercise [ 43 , 44 ], so that the children can gradually adapt and not have fear of the pain caused by the functional exercise of the affected limb, and increase their compliance with the early functional exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The general exercise method is from simple to complex, time from short to long, frequency from less to more, the intensity of exercise gradually increases, and the transition from passive exercise to active exercise gradually [ 41 , 42 ]. It is appropriate for the child to accept and not cause severe pain, and if necessary, give appropriate analgesics in accordance with the doctor's instructions before the exercise [ 43 , 44 ], so that the children can gradually adapt and not have fear of the pain caused by the functional exercise of the affected limb, and increase their compliance with the early functional exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The pediatric fracture volume has decreased during the COVID-19 pandemic, partially, because of the cessation of organized sports and decreased playground use. In China, home confinement led to a significant reduction in the number of pediatric fractures, which decreased from 5346 patients in 2017–2019 to 862 patients in 2020 [ 26 ]. A similar finding was observed in the Korean population.…”
Section: Discussionmentioning
confidence: 99%
“…We retrospectively compared children admitted to a tertiary pediatric hospital in China [ 25 ] for traumatic injury between January 24 and March 10, 2020, to those admitted within the same period from 2017 to 2019. Children with fractures were compared in terms of etiology, fracture location, sex, and age to evaluate the effects of home confinement on the epidemiology of pediatric fractures during the COVID-19 pandemic.…”
Section: Changes In Pediatric Upper-extremity Fracture Patterns Since...mentioning
confidence: 99%
“…A retrospective review in China [ 25 ] reported that the number of tibial fractures decreased from 208 to 52, femoral from 192 to 32, and fibular from 78 to 28, while the surgery rate changed from 9.38% to 34.38% for the femur and from 6.73% to 5.77% for the tibia. Although the overall number of pediatric lowerextremity fracture patients decreased, the change in the number of injured patients requiring surgery for treatment did not change significantly, suggesting increased numbers of surgeries.…”
Section: Changes In Pediatric Lower-extremity Fracture Patterns After...mentioning
confidence: 99%
See 1 more Smart Citation